Food-borne trematodes - Stothard, Russell (Henry Stewart Talks, 2020)
Liver fluke disease on a global scale, Liver cancer associated with liver flukes, Zoonotic potential of liver flukes and their natural history, Diagnosing liver fluke, Treatment of liver fluke